Impact of Facultative Bacteria on the Metabolic Function of an Obligate Insect-Bacterial Symbiosis - Frances Blow (American Society for Microbiology, 2020)
ABSTRACT Beneficial microorganisms associated with animals derive their nutritional requirements entirely from the animal host, but the impact of these microorganisms on host metabolism is largely unknown. The focus of this study was the experimentally tractable tripartite symbiosis between the pea aphid Acyrthosiphon pisum, its obligate intracellular bacterial symbiont Buchnera, and the facultative bacterium Hamiltonella which is localized primarily to the aphid hemolymph (blood). Metabolome experiments on, first, multiple aphid genotypes that naturally bear or lack Hamiltonella and, second, one aphid genotype from which Hamiltonella was experimentally eliminated revealed no significant effects of Hamiltonella on aphid metabolite profiles, indicating that Hamiltonella does not cause major reconfiguration of host metabolism. However, the titer of just one metabolite, 5-aminoimidazole-4-carboxamide ribonucleotide (AICAR), displayed near-significant enrichment in Hamiltonella-positive aphids in both metabolome experiments. AICAR is a by-product of biosynthesis of the essential amino acid histidine in Buchnera and, hence, an index of histidine biosynthetic rates, suggesting that Buchnera-mediated histidine production is elevated in Hamiltonella-bearing aphids. Consistent with this prediction, aphids fed on [13C]histidine yielded a significantly elevated 12C/13C ratio of histidine in Hamiltonella-bearing aphids, indicative of increased (∼25%) histidine synthesized de novo by Buchnera. However, in silico analysis predicted an increase of only 0.8% in Buchnera histidine synthesis in Hamiltonella-bearing aphids. We hypothesize that Hamiltonella imposes increased host demand for histidine, possibly for heightened immune-related functions. These results demonstrate that facultative bacteria can alter the dynamics of host metabolic interactions with co-occurring microorganisms, even when the overall metabolic homeostasis of the host is not substantially perturbed. IMPORTANCE Although microbial colonization of the internal tissues of animals generally causes septicemia and death, various animals are persistently associated with benign or beneficial microorganisms in their blood or internal organs. The metabolic consequences of these persistent associations for the animal host are largely unknown. Our research on the facultative bacterium Hamiltonella, localized primarily to the hemolymph of pea aphids, demonstrated that although Hamiltonella imposed no major reconfiguration of the aphid metabolome, it did alter the metabolic relations between the aphid and its obligate intracellular symbiont, Buchnera. Specifically, Buchnera produced more histidine in Hamiltonella-positive aphids to support both Hamiltonella demand for histidine and Hamiltonella-induced increase in host demand. This study demonstrates how microorganisms associated with internal tissues of animals can influence specific aspects of metabolic interactions between the animal host and co-occurring microorganisms.